Designing Aspects and Classification of Bearing Industry Box Handling Apparatus - Tiba, Zsolt; Fekete-Szűcs, Dániel (International Journal of Engineering and Management Sciences, 2019)
It has been an accepted tendency in the industrial practice since the last third of the 20th Century to decrease the living labour demand of the manufacturing processes. One of the main tools of it is the automation of production. In the design, the construction and the programming of the developed automata, the results of electronics, informatics and mechatronics can be used. All of the scientific fields mentioned above undergo intensive development. By the application of the results achieved in the design of the applications, the monotonous, dangerous and tiresome work not requiring expertise can be assigned to machines. In the longer run, the application of the automata is beneficial also in financial aspect, since the costs of living labour are continuously growing, while that of the mechatronic and technological devices show a rather decreasing tendency. Reliability is also an important aspect. It is well known for everyone that a well-designed and programmed automatic device performs its task without mistakes. If there is any objection or breakdown, on the basis of the currently valid safety technology rules, the machine stops, does not trigger any damage and after its repair, work can be continued.